Association between patient age, microcirculation, and coronary stenosis assessment with fractional flow reserve and instantaneous wave‐free ratio. Issue 4 (23rd January 2022) - Mejia‐Renteria, Hernan; Faria, Daniel; Lee, Joo Myung; Lee, Seung Hun; Jung, Ji‐Hyun; Doh, Joon‐Hyung; Nam, Chang‐Wook; Shin, Eun‐Seok; Hoshino, Masahiro; Sugiyama, Tomoyo; Kanaji, Yoshihisa; Gonzalo, Nieves; et al.
Abstract: Objectives: To investigate the effect of aging on coronary stenosis functional assessment with fractional flow reserve (FFR) and instantaneous wave‐free ratio (iFR). Background: Limited data exist regarding the impact of patient age on these coronary pressure indices. Methods: We analyzed 514 patients with coronary stenosis interrogated with intravascular physiology. The influence of patient age on FFR, iFR, and microcirculation‐related indices was investigated. Vessel‐oriented composite outcome (VOCO) was assessed in the FFR‐based deferred population according to iFR, coronary flow reserve (CFR), and age. Results: FFR increased ( r = 0.128, p = 0.004), iFR remained unchanged ( r = −0.001, p = 0.980), and CFR decreased ( r = −0.095, p = 0.001) with patient age. Relationship between FFR and CFR differed across age groups ( r = 0.263 in <60 years old vs. r = 0.124 in ≥60 years old, p = 0.0056), whereas iFR correlated to CFR similarly regardless age ( r = 0.283 in <60 years old vs. r = 0.219 in ≥60 years old, p = 0.3781). No differences were found on angiographic stenosis severity (%DS 47.4 in <60 years old and 49.8 in ≥60 years old, p = 0.317). At 5 years, FFR‐based revascularisation deferral in patients ≥60 years old was associated with more VOCO when either iFR (25%) or CFR (16.9%) were abnormal, compared to patients with normal iFR (6.3%) or normal CFR (4.6%) (log‐rank p < 0.001). This difference in clinical outcomes was not observed in younger patients. Conclusions: FFR values increased progressively with patient age, potentially associated with age‐related changes in the coronary microcirculation. Conversely, iFR values remained unchanged across the patient age spectrum. In ≥60 years old patients with revascularisation deferral based on FFR, both abnormal iFR and CFR values were associated with worse long‐term patient outcomes.